Skeleton-Structure WS2@CNT Thin-Film Hybrid Electrodes for High-Performance Quasi-Solid-State Flexible Supercapacitors - Yang, Xinyu; Li, Jiahui; Hou, Chengyi; Zhang, Qinghong; Li, Yaogang; Wang, Hongzhi (Frontiers in Chemistry, 2020)
The purpose of this work is to explore the application prospects of WS2 as an active material in flexible electrodes. Since WS2 has similar disadvantages as other two-dimensional layered materials, such as easily stacking, it is essential to develop a three-dimensional structure for its assembly in terms of electrochemical performance. In addition, the low conductivity of WS2 limits its application as flexible electrode material. In order to solve these problems, carbon nanotubes (CNTs) are introduced to improve the conductivity of hybrid WS2 materials and to construct a skeleton structure during WS2 assembly. Compared with pure CNTs and WS2, the WS2@CNT thin-film hybrid with a unique skeleton structure has a high specific area capacitance that reaches a maximum of 752.53 mF/cm2 at a scan rate 20 mV/s. Meanwhile, this hybrid electrode material shows good stability, with only 1.28% loss of its capacitance over 10,000 cycles. In order to prove its feasibility for practical application, a quasi-solid-state flexible supercapacitor is assembled, and its electrochemical characteristics (the specific area capacitance is 574.65 mF/cm2) and bendability (under bending to 135° 10, 000 times, 23.12% loss at a scan rate of 100 mV/s) are further investigated and prove its potential in this field.